A Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy and preparation method thereof

The Yb-Sc alloyed Al-Mg-Zn-Ag alloy addresses the limitations of existing Al-Mg alloys by forming nano-scale phases and dispersion strengthening, achieving ultra-high strength and corrosion resistance through a controlled process, surpassing conventional alloys in mechanical properties and production efficiency.

CN117265347BActive Publication Date: 2024-12-17CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311435669.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-01
Publication Date
2024-12-17
Estimated Expiration
2043-11-01

AI Technical Summary

Technical Problem

Existing 5XXX series Al-Mg alloys have low tensile and yield strengths, limited strength improvement, and high production costs due to the use of rare earth elements like Sc, and existing Al-Mg-Zn alloys do not achieve sufficient ultra-high strength and corrosion resistance.

Method used

A Yb-Sc alloyed Al-Mg-Zn-Ag alloy with controlled compositions and a double-stage heat treatment process to form nano-scale T-Mg 32(Al, Zn) 49 and β(Mg2Zn) phases, combined with dispersion strengthening and grain refinement, to enhance mechanical properties.

Benefits of technology

The alloy achieves ultra-high tensile strength exceeding 560 MPa with excellent corrosion resistance and low density, outperforming conventional alloys in mechanical properties and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000008168500000091
    Figure GHA0000008168500000091
Patent Text Reader

Abstract

The present invention relates to a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy and a preparation method thereof. The alloy is composed of the following components in mass percentage: Mg 4.0-10.0%, Zn 2.0-6.0%, Ag 0.1-3.0%, Zr 0.05-0.2%, Mn 0.05-0.3%, Yb 0.01-0.2%, Sc 0.01-0.08%, Mg / Zn mass ratio 1.5-4.5, and the remainder is Al. The preparation method is: according to the designed aluminum alloy component ratio, each component is weighed, and an ingot is formed by smelting and casting, and then subjected to two-stage soaking treatment, rolling or hot extrusion, solid solution and two-stage aging heat treatment. The present invention can regulate the distribution and morphology of the microstructure and precipitated phase by regulating the composition and process of the alloy, obtain excellent comprehensive performance, and can be suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy and a preparation method thereof, belonging to the field of nonferrous metal materials. Background Art

[0002] In order to improve the fuel economy of aircraft, transportation, ships and other fields, save energy and reduce emissions, it has become an inevitable development trend to conduct lightweight research in various manufacturing fields. 5XXX series Al-Mg alloys have good corrosion resistance, formability and weldability, and have been widely used, but the tensile strength (about 200-300MPa) and yield strength (about 100-250MPa) of its industrialized alloys are both low, and the yield strength ratio (yield strength to tensile strength) is low, generally lower than 0.7, because it relies on Mg elements for solid solution strengthening and work hardening, and the strength improvement is limited. Adding 0.1-0.3% of rare earth elements Sc to Al-Mg alloys can improve the strength of Al-Mg alloys, and the tensile strength can reach 400MPa, the yield strength can reach 300MPa, and the yield strength ratio can reach 0.75, but the overall strength is still low. However, the price of rare earth Sc is expensive, and the addition of 0.1-0.3% Sc increases the production cost of Al-Mg alloys. The Chinese patent (application number 201910256350.7) proposes adding 1-2% Zn to Al-Mg alloy, which improves the strength of the alloy. The tensile strength of the alloy is lower than 490MPa and the yield strength is lower than 410MPa.

[0003] On this basis, the present invention proposes a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy and a preparation method thereof, the purpose of which is to obtain ultra-high strength while maintaining the low density and corrosion resistance of the alloy, so as to prepare a new generation of aluminum alloy plates or bars with excellent comprehensive performance. Summary of the invention

[0004] In order to meet the requirements of the lightweight manufacturing field, the first object of the present invention is to provide an ultra-high strength Al-Mg-Zn-Ag alloy alloyed with Yb-Sc. The Al-Mg-Zn-Ag alloy provided by the present invention has ultra-high strength while maintaining the low density and corrosion resistance of the alloy.

[0005] The second object of the present invention is to provide a method for preparing a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy.

[0006] The invention discloses a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy, which consists of the following components by mass percentage: 4.0-10.0% Mg, 2.0-6.0% Zn, 0.1-3.0% Ag, 0.05-0.2% Zr, 0.05-0.3% Mn, 0.01-0.2% Yb, 0.01-0.08% Sc, Mg / Zn mass ratio of 1.5-4.5, and the balance of Al.

[0007] The present invention provides an Al-Mg-Zn-Ag alloy, which uses Mg and Zn as main strengthening elements and controls the composition within the scope of the present invention to obtain nano-scale T-Mg 32 (Al, Zn) 49 Phase and β(Mg2Zn) dual-phase structural strengthening phase, T phase has better strengthening effect. A large number of fine and dispersed T phases will be precipitated during the solid solution aging process, which is helpful to improve the strength of the alloy and maintain low density and good corrosion resistance. The added Ag element is dissolved into the aluminum matrix, which has a solid solution strengthening effect and promotes T-Mg 32 (Al, Zn) 49 The addition of trace elements such as Yb, Sc and Zr helps to obtain dispersed multi-element Al3 (Yb, Sc, Zr) phase particles in the matrix, which has the effect of dispersion strengthening and grain refinement, and inhibits recovery recrystallization. In addition, the addition of trace elements such as Mn helps to reduce the harmful effects of impurity elements such as Fe and Si in the alloy. The formed dispersed Al6Mn phase can inhibit the recrystallization of the alloy, thereby further improving the mechanical properties of the alloy. With the synergy of the above-mentioned components and contents, the ultra-high strength Al-Mg-Zn-Ag alloy provided by the present invention has a tensile strength of more than 560 MPa and excellent corrosion resistance.

[0008] The invention discloses a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy, which consists of the following components by mass percentage: 5.0-8.0% Mg, 2.0-5.0% Zn, 0.1-2.0% Ag, 0.05-0.15% Zr, 0.05-0.15% Mn, 0.01-0.1% Yb, 0.01-0.05% Sc, Mg / Zn mass ratio of 1.75-4, and the balance of Al.

[0009] The invention discloses a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy, which is composed of the following components by mass percentage: Mg 7.0-8.0%, Zn 2.0-5.0%, Ag 0.3-1.5%, Zr 0.1-0.15%, Mn 0.05-0.15%, Yb 0.01-0.1%, Sc 0.01-0.04%, Mg / Zn mass ratio 1.75-4, and the balance Al. Within the preferred composition range, the tensile strength of the obtained ultra-high strength Al-Mg-Zn-Ag alloy is as high as 630MPa or more.

[0010] The invention discloses a preparation method of a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy. The method comprises the following steps: preparing pure Al, pure Mg, pure Zn, pure Ag, Al-Yb master alloy, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy according to the designed aluminum alloy component ratio, smelting to obtain molten alloy liquid, pouring the molten alloy liquid into a mold to crystallize into an ingot, and sequentially performing a double-stage soaking treatment, rolling or extrusion, solid solution treatment and aging treatment on the ingot to obtain the alloy.

[0011] The preparation method of the present invention comprises the following steps: after obtaining the ingot, the ingot is first subjected to a double-stage soaking treatment, so that the non-equilibrium solidification phase formed in the casting process is fully dissolved in the matrix, the non-equilibrium phase at the grain boundary is reduced, and the adverse effect of the non-equilibrium relative strength at the grain boundary is reduced; at the same time, a multi-component Al3 (Yb, Sc, Zr) phase is dispersed in the ingot; then, the dendrites in the soaking treated ingot are broken by rolling or extrusion, the grains are refined, and at the same time, the multi-component Al3 (Yb, Sc, Zr) phase dispersed and precipitated in the soaking treatment is regulated to recover and recrystallize; then, after the solid solution, a double-stage aging treatment is performed to precipitate a nano-scale T-Mg 32 (Al, Zn) 49 phase and β(Mg2Zn) dual-phase structural strengthening phase, thereby obtaining an ultra-high strength Al-Mg-Zn-Ag alloy alloyed with Yb-Sc.

[0012] The Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy provided by the present invention is composite alloyed with rare earth Yb and Sc, and an ultra-high strength corrosion-resistant aluminum alloy with excellent room temperature mechanical properties is obtained by regulating the contents of main elements (Mg, Zn), strengthening elements (Ag), grain refinement and recovery recrystallization inhibition elements (Yb, Sc, Zr, Mn), and coordinated isothermal heat treatment process, rolling or hot extrusion process, and solid solution and aging process conditions. The obtained aluminum alloy has low density, corrosion resistance and ultra-high strength. The preparation process provided by the present invention is simple and can realize industrial production.

[0013] As a preferred scheme, the process of the double-stage heat treatment is: first heat to the first-stage heat treatment temperature, keep warm for 12 to 24 hours, and then heat to the second-stage heat treatment temperature, keep warm for 5 to 24 hours. The first-stage heat treatment temperature is 400 to 450°C, and the second-stage heat treatment temperature is 450 to 500°C. The second-stage heat treatment temperature is more than 30°C higher than the first-stage heat treatment temperature, preferably 30 to 80°C.

[0014] As a preferred solution, the rolling is hot rolling, and the hot rolling temperature is 400-460°C.

[0015] As a preferred solution, the extrusion temperature is 400-430°C, and the extrusion ratio is 5-20.

[0016] As a preferred solution, the temperature of the solution treatment is 430-500° C., the time of the solution treatment is 1-5 hours, and after the solution treatment is completed, the steel is rapidly cooled to room temperature for quenching treatment.

[0017] As a preferred solution, the aging treatment adopts double-stage aging, the temperature of the first stage aging treatment is 80-110°C, the time of the first stage aging treatment is 20-48h, the temperature of the second stage aging treatment is 120-180°C, and the time of the second stage aging treatment is 10-40h.

[0018] The ultra-high strength Al-Mg-Zn-Ag alloy alloyed with Yb-Sc prepared by this process has a density lower than 2.7 g / cm 3 The corrosion resistance is higher than that of EA grade, and the strength can reach 660MPa in the preferred solution.

[0019] Features of the present invention:

[0020] The present invention provides an Al-Mg-Zn-Ag alloy, which uses Mg and Zn as main strengthening elements and controls the composition within the scope of the present invention to obtain nano-scale T-Mg 32 (Al, Zn) 49 Phase and β(Mg2Zn) dual-phase structural strengthening phase, T phase has better strengthening effect. A large number of fine and dispersed T phases will be precipitated during the solid solution aging process, which is helpful to improve the strength of the alloy and maintain low density and good corrosion resistance. The added Ag element is dissolved into the aluminum matrix, which has a solid solution strengthening effect and promotes T-Mg 32 (Al, Zn) 49The addition of trace elements such as Yb, Sc and Zr helps to obtain dispersed multi-element Al3 (Yb, Sc, Zr) phase particles in the matrix, which has the effect of dispersion strengthening and grain refinement, and inhibits recovery recrystallization. In addition, the addition of trace elements such as Mn helps to reduce the harmful effects of impurity elements such as Fe and Si in the alloy. The formed dispersed Al6Mn phase can inhibit the recrystallization of the alloy, thereby further improving the mechanical properties of the alloy. With the synergy of the above-mentioned components and contents, the ultra-high strength Al-Mg-Zn-Ag alloy provided by the present invention has a tensile strength of more than 560 MPa and excellent corrosion resistance.

[0021] The present invention controls the content and ratio of the main elements Mg and Zn, adds the solid solution strengthening element Ag, regulates the content of the grain refinement and recovery recrystallization elements Yb, Sc and Zr, and optimizes the process conditions of the solid solution and aging treatment, thereby obtaining an ultra-high strength Al-Mg-Zn-Ag alloy of Yb-Sc alloying with excellent comprehensive performance. The obtained aluminum alloy has low density and corrosion resistance, and the tensile strength of the alloy can reach more than 560MPa, achieving the effect of ultra-high strength Al-Zn-Mg-Cu, but the comprehensive performance is better than that of the existing Al-Mg alloy. DETAILED DESCRIPTION

[0022] Comparative Example 1

[0023] The composition and weight percentage of the alloy are Al-4Mg-1Zn-0.15Sc. The preparation method comprises the following steps: (1) weighing each component according to the designed aluminum alloy composition ratio, melting pure Al, pure Mg, pure Zn and Al-Sc master alloy at high temperature by resistance furnace smelting, degassing and deslagging, obtaining molten alloy liquid, and casting into ingots; (2) subjecting the ingot obtained in step (1) to single-stage isothermal heat treatment at a heat treatment temperature of 500°C, and obtaining a homogenized ingot after holding for 12 hours; (3) subjecting the homogenized ingot obtained in step (2) to hot extrusion treatment at an extrusion temperature of 430°C and an extrusion ratio of 20; (4) subjecting the extruded plate to solid solution treatment at a solid solution temperature of 430°C and a holding time of 5 hours; (5) subjecting the solid solution treated plate to bipolar aging treatment at a first-stage aging temperature of 80°C and a holding time of 48 hours, and a second-stage aging temperature of 120°C and a holding time of 24 hours. The mechanical properties test results are shown in Table 1.

[0024] Comparative Example 2

[0025] The composition and weight percentage of the alloy are Al-10Mg-4Zn-0.1Sc. The preparation method is as follows: (1) According to the designed aluminum alloy composition ratio, weigh each component, melt pure Al, pure Mg, pure Zn and Al-Sc master alloy at high temperature by resistance furnace smelting, degas and slag refinement, obtain molten alloy liquid, and cast into ingot; (2) The ingot obtained in step (1) is subjected to single-stage isothermal heat treatment, the heat treatment temperature is 480°C, and the ingot is obtained after 24 hours of heat preservation; (3) The ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 400°C, and the extrusion ratio is 5; (4) The plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 400°C, and the heat preservation time is 2h; (5) The plate treated with solid solution is subjected to single-stage aging treatment, the aging temperature is 150°C, and the heat preservation time is 48h. The mechanical properties test results are shown in Table 1.

[0026] Comparative Example 3

[0027] The composition and weight percentage of the alloy are Al-7Mg-4Zn-0.1Sc. The preparation method is as follows: (1) According to the designed aluminum alloy composition ratio, weigh each component, melt pure Al, pure Mg, pure Zn and Al-Sc master alloy at high temperature by resistance furnace smelting and degassing and deslagging to obtain molten alloy liquid, and cast it into an ingot; (2) The ingot obtained in step (1) is subjected to single-stage isothermal heat treatment at a heat treatment temperature of 480°C, and a homogenized ingot is obtained after 24 hours of heat preservation; (3) The homogenized ingot obtained in step (2) is subjected to hot rolling treatment at a rolling temperature of 420°C; (4) The plate obtained by rolling is subjected to solid solution treatment at a solid solution temperature of 450°C and a heat preservation time of 1 hour; (5) The plate subjected to solid solution treatment is subjected to single-stage aging treatment at an aging temperature of 180°C and a heat preservation time of 10 hours. The mechanical properties test results are shown in Table 1.

[0028] Comparative Example 4

[0029] The composition and weight percentage of the alloy are Al-4Mg-1Zn-0.3Mn-0.1Sc. The preparation method is as follows: (1) According to the designed aluminum alloy composition ratio, weigh each component, melt pure Al, pure Mg, pure Zn, Al-Mn master alloy and Al-Sc master alloy at high temperature by resistance furnace smelting, degas and slag refinement, obtain molten alloy liquid, and cast into ingot; (2) The ingot obtained in step (1) is subjected to single-stage isothermal heat treatment, the heat treatment temperature is 500°C, and the ingot is obtained after being kept warm for 12 hours; (3) The ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 430°C, and the extrusion ratio is 20; (4) The plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 5 hours; (5) The plate treated with solid solution is subjected to single-stage aging treatment, the aging temperature is 120°C, and the heat preservation time is 48 hours. The mechanical properties test results are shown in Table 1.

[0030] Comparative Example 5

[0031] The composition and weight percentage of the alloy are Al-7Mg-3Zn-1Cu-1Mn-0.5Sc. The preparation method comprises the following steps: (1) weighing each component according to the designed aluminum alloy composition ratio, melting pure Al, pure Mg, pure Zn, pure Cu, Al-Mn master alloy and Al-Sc master alloy at high temperature by resistance furnace smelting, degassing and deslagging, obtaining molten alloy liquid, and casting into ingots; (2) isothermal heat treatment of the ingot obtained in step (1), the heat treatment temperature is 500°C, and the ingot is obtained after being kept warm for 24 hours; (3) the ingot obtained in step (2) is hot extrusion treatment, the extrusion temperature is 400°C, and the extrusion ratio is 10; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 1 hour; (5) the plate treated with solid solution is subjected to single-stage aging treatment, the aging temperature is 150°C, and the heat preservation time is 30 hours. The mechanical properties test results are shown in Table 1.

[0032] Comparative Example 6

[0033] The composition and weight percentage of the alloy are Al-4Mg-1Zn-0.3Mn. The preparation method is as follows: (1) According to the designed aluminum alloy composition ratio, weigh each component, melt pure Al, pure Mg, pure Zn and Al-Mn master alloy at high temperature by resistance furnace smelting and degassing and deslagging to obtain molten alloy liquid, and cast it into an ingot; (2) The ingot obtained in step (1) is subjected to isothermal heat treatment at a heat treatment temperature of 500°C, and after keeping the temperature for 12 hours, a homogenized ingot is obtained; (3) The homogenized ingot obtained in step (2) is subjected to hot extrusion treatment at an extrusion temperature of 430°C and an extrusion ratio of 20; (4) The plate obtained by extrusion is subjected to solid solution treatment at a solid solution temperature of 430°C and a heat preservation time of 5 hours; (5) The plate treated with solid solution is subjected to single aging treatment at an aging temperature of 120°C and a heat preservation time of 48 hours. The mechanical properties test results are shown in Table 1.

[0034] Comparative Example 7

[0035] The composition and weight percentage of the alloy are Al-4Mg-1Zn-0.3Mn-0.1Sc. The preparation method is as follows: (1) According to the designed aluminum alloy composition ratio, weigh each component, melt pure Al, pure Mg, pure Zn, Al-Mn master alloy and Al-Sc master alloy at high temperature by resistance furnace smelting, degas and slag refinement, obtain molten alloy liquid, and cast into ingot; (2) The ingot obtained in step (1) is subjected to isothermal heat treatment at a heat treatment temperature of 500°C, and a homogenized ingot is obtained after holding for 12 hours; (3) The homogenized ingot obtained in step (2) is subjected to hot extrusion treatment at an extrusion temperature of 430°C and an extrusion ratio of 20; (4) The plate obtained by extrusion is subjected to solid solution treatment at a solid solution temperature of 430°C and a holding time of 5 hours; (5) The plate subjected to solid solution treatment is subjected to single-stage aging treatment at an aging temperature of 80°C and a holding time of 48 hours. The mechanical properties test results are shown in Table 1.

[0036] Example 1

[0037] The components of the alloy and their weight percentages are Al-4Mg-2Zn-0.1Ag-0.05Zr-0.01Yb-0.01Sc-0.05Mn, and the mass ratio of Mg / Zn is 2. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 400°C and keeping it for 12 hours, and then heating to 480°C and keeping it for 24 hours; (3) the homogenized ingot obtained in step (2) is rolled at a rolling temperature of 400°C; (4) the plate obtained by rolling is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 5 hours; (5) the plate treated with solid solution is subjected to bipolar aging treatment, the first stage aging temperature is 80°C, the heat preservation time is 48 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 24 hours. The mechanical properties test results are shown in Table 1.

[0038] Example 2

[0039] The components of the alloy and their weight percentages are Al-4Mg-2Zn-0.1Ag-0.05Zr-0.01Yb-0.01Sc-0.05Mn, and the mass ratio of Mg / Zn is 2. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, the heat treatment process is: heating to 400°C and keeping it for 12 hours, and then heating to 480°C and keeping it for 24 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 400°C, and the extrusion ratio is 5; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 5 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 80°C, the heat preservation time is 48 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 24 hours. The mechanical properties test results are shown in Table 1.

[0040] Example 3

[0041] The components of the alloy and their weight percentages are Al-7Mg-4Zn-1.5Ag-0.1Zr-0.1Yb-0.04Sc-0.1Mn, and the mass ratio of Mg / Zn is 1.75. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, the heat treatment process is: heating to 450°C and keeping it for 24 hours, and then heating to 500°C and keeping it for 1 hour; (3) the homogenized ingot obtained in step (2) is rolled at a rolling temperature of 460°C; (4) the plate obtained by rolling is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 5 hours; (5) the plate treated with solid solution is subjected to bipolar aging treatment, the first stage aging temperature is 110°C, the heat preservation time is 20 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 40 hours. The mechanical properties test results are shown in Table 1.

[0042] Example 4

[0043] The components of the alloy and their weight percentages are Al-7Mg-4Zn-1.5Ag-0.1Zr-0.1Yb-0.04Sc-0.1Mn, and the mass ratio of Mg / Zn is 1.75. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 450°C and keeping warm for 24 hours, and then heating to 500°C and keeping warm for 5 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 430°C, and the extrusion ratio is 20; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 460°C, and the heat preservation time is 3 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 80°C, the heat preservation time is 48 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 24 hours. The mechanical properties test results are shown in Table 1.

[0044] Example 5

[0045] The components of the alloy and their weight percentages are Al-10Mg-6Zn-3Ag-0.2Zr-0.1Yb-0.04Sc-0.3Mn, and the mass ratio of Mg / Zn is 1.67. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 450°C and keeping warm for 24 hours, and then heating to 500°C and keeping warm for 3 hours; (3) the homogenized ingot obtained in step (2) is rolled at a rolling temperature of 460°C; (4) the plate obtained by rolling is subjected to solid solution treatment, the solid solution temperature is 430°C, and the heat preservation time is 5 hours; (5) the plate treated with solid solution is subjected to bipolar aging treatment, the first stage aging temperature is 110°C, the heat preservation time is 20 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 40 hours. The mechanical properties test results are shown in Table 1.

[0046] Example 6

[0047] The components of the alloy and their weight percentages are Al-7Mg-4Zn-1.5Ag-0.1Zr-0.1Yb-0.04Sc-0.15Mn, and the mass ratio of Mg / Zn is 1.75. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar soaking treatment, and the soaking process is: heating to 430°C and keeping it for 16 hours, and then heating to 480°C and keeping it for 12 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 420°C, and the extrusion ratio is 12; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 480°C, and the heat preservation time is 5 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 80°C, the heat preservation time is 35 hours, and the second stage aging temperature is 150°C, and the heat preservation time is 24 hours. The mechanical properties test results are shown in Table 1.

[0048] Example 7

[0049] The components of the alloy and their weight percentages are Al-5Mg-2Zn-0.1Ag-0.05Zr-0.01Yb-0.01Sc-0.15Mn, and the mass ratio of Mg / Zn is 2.5. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 410°C and keeping it for 18 hours, and then heating to 480°C and keeping it for 24 hours; (3) the homogenized ingot obtained in step (2) is hot rolled at a rolling temperature of 430°C; (4) the plate obtained by rolling is subjected to solid solution treatment at a solid solution temperature of 490°C and a holding time of 3 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 100°C and the holding time is 30 hours, and the second stage aging temperature is 150°C and the holding time is 24 hours. The mechanical properties test results are shown in Table 1.

[0050] Example 8

[0051] The components of the alloy and their weight percentages are Al-5Mg-2Zn-0.1Ag-0.05Zr-0.01Yb-0.01Sc-0.15Mn, and the mass ratio of Mg / Zn is 2.5. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 410°C and keeping it for 18 hours, and then heating to 480°C and keeping it for 24 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 420°C, and the extrusion ratio is 15; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 490°C, and the heat preservation time is 3 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 100°C, the heat preservation time is 30 hours, and the second stage aging temperature is 150°C, and the heat preservation time is 24 hours. The mechanical properties test results are shown in Table 1.

[0052] Example 9

[0053] The components of the alloy and their weight percentages are Al-8Mg-5Zn-2Ag-0.15Zr-0.01Yb-0.01Sc-0.05Mn, and the mass ratio of Mg / Zn is 1.6. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 410°C and keeping it for 18 hours, and then heating to 480°C and keeping it for 24 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 430°C, and the extrusion ratio is 10; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 500°C, and the heat preservation time is 1 hour; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 110°C, the heat preservation time is 20 hours, and the second stage aging temperature is 150°C, and the heat preservation time is 30 hours. The mechanical properties test results are shown in Table 1.

[0054] Example 10

[0055] The components of the alloy and their weight percentages are Al-8Mg-4Zn-0.3Ag-0.10Zr-0.1Yb-0.04Sc-0.06Mn, and the mass ratio of Mg / Zn is 2. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 420°C and keeping it for 15 hours, and then heating to 450°C and keeping it for 20 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 420°C, and the extrusion ratio is 8; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 480°C, and the heat preservation time is 2 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 90°C, the heat preservation time is 25 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 40 hours. The mechanical properties test results are shown in Table 1.

[0056] Embodiment 11

[0057] The components of the alloy and their weight percentages are Al-8Mg-2Zn-0.3Ag-0.10Zr-0.06Yb-0.04Sc-0.08Mn, and the Mg / Zn mass ratio is 4. The following steps are as follows: (1) according to the designed aluminum alloy component ratio, weigh each component, use a resistance furnace to melt pure Al, pure Mg, pure Zn, pure Ag, Al-Zr master alloy, Al-Sc master alloy and Al-Mn master alloy at high temperature, degas and deslag refine, obtain molten alloy liquid, and cast it into an ingot; (2) the ingot obtained in step (1) is subjected to bipolar heat treatment, and the heat treatment process is: heating to 420°C and keeping it for 15 hours, and then heating to 450°C and keeping it for 20 hours; (3) the homogenized ingot obtained in step (2) is subjected to hot extrusion treatment, the extrusion temperature is 420°C, and the extrusion ratio is 8; (4) the plate obtained by extrusion is subjected to solid solution treatment, the solid solution temperature is 480°C, and the heat preservation time is 2 hours; (5) the plate subjected to solid solution treatment is subjected to bipolar aging treatment, the first stage aging temperature is 90°C, the heat preservation time is 25 hours, and the second stage aging temperature is 120°C, and the heat preservation time is 40 hours. The mechanical properties test results are shown in Table 1.

[0058] Table 1 Room temperature properties of the alloy of the present invention

[0059]

[0060] Comparing the performance parameter values ​​of the embodiment and the comparative example, it can be seen that the Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy prepared by the present invention has excellent comprehensive performance, which indicates that the present invention enables the embodiment alloy to have room temperature mechanical properties and corrosion resistance better than the comparative example alloy through the interaction of alloy components and the synergistic effect of the process.

Claims

1. A method for preparing a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy, characterized in that: Pure Al, pure Mg, pure Zn, pure Ag, Al-Yb master alloy, Al-Zr master alloy, Al-Sc master alloy, and Al-Mn master alloy are prepared according to the designed component ratio of the Al-Mg-Zn-Ag alloy, and molten alloy liquid is obtained by smelting, and the molten alloy liquid is poured into a mold to crystallize into an ingot, and the ingot is sequentially subjected to a double-stage soaking treatment, rolling or extrusion, solid solution treatment, and aging treatment to obtain the obtained product; The process of the double-stage heat treatment is: firstly heat to the first-stage heat treatment temperature, keep it at that temperature for 12 to 24 hours, then heat to the second-stage heat treatment temperature, keep it at that temperature for 5 to 24 hours, the first-stage heat treatment temperature is 400 to 450°C, the second-stage heat treatment temperature is 450 to 500°C, and the second-stage heat treatment temperature is higher than the first-stage heat treatment temperature by more than 30°C; The rolling is hot rolling, and the hot rolling temperature is 400-460°C; The extrusion temperature of the extrusion is 400-430°C, and the extrusion ratio is 5-20; The ultra-high strength Al-Mg-Zn-Ag alloy is composed of the following components, in terms of mass percentage: Mg 7.0-8.0%, Zn 2.0-5.0%, Ag 0.3-1.5%, Zr 0.1-0.15%, Mn 0.05-0.15%, Yb 0.01-0.1%, Sc 0.01-0.04%, Mg / Zn mass ratio 1.75-4, and the balance is Al; The tensile strength of the ultra-high strength Al-Mg-Zn-Ag alloy is above 560 MPa.

2. The method for preparing a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy according to claim 1, characterized in that: The temperature of the solution treatment is 430-500° C., the time of the solution treatment is 1-5 hours, and after the solution treatment is completed, the steel is rapidly cooled to room temperature for quenching treatment.

3. The method for preparing a Yb-Sc alloyed ultra-high strength Al-Mg-Zn-Ag alloy according to claim 1, characterized in that: The aging treatment adopts double-stage aging, the temperature of the first stage aging treatment is 80-110° C., the time of the first stage aging treatment is 20-48 hours, the temperature of the second stage aging treatment is 120-180° C., and the time of the second stage aging treatment is 10-40 hours.